Long-term oncological outcomes of organ-sparing treatment of patients with early breast cancer aged 65 years and older who had no postoperative radiation therapy - D. R. Ortabaeva; A. D. Zikiryakhodzhaev; E. A. Rasskazova; E. K. Saribekyan; A. D. Kaprin (ABV-press, 2022)
Postoperative radiation therapy after breast-conserving surgery is a standard method of treating breast cancer, but recently the issue of its de-escalation in patients older than 65 due to concomitant pathology, lower life expectancy and possible development of post-radiation complications has been discussed. The results of some foreign studies prove the absence of a statistically significant difference in relapse-free and overall survival in patients with early breast cancer older than 65 years with relatively favorable clinical and morphological characteristics without postoperative radiation therapy. We analyzed the long-term oncological results in patients with breast cancer older than 65 years after breast-conserving surgery without postoperative radiation therapy. The results of the study showed that postoperative radiation therapy in patients over 65 years of age with stage IA pT1N0M0 breast cancer of luminal immunophenotype A does not improve long-term oncological indicators. Thus, the exclusion of postoperative radiation therapy from the treatment plan of this group of patients is oncologically safe and economically justified.